Implementation of Fiqh Rules in Economic Transactions in Islamic Financial Institutions: A Literature Review Study - Nasrullah; Muthoifin (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the implementation of fiqh rules in economic transactions in Islamic financial institutions through a literature review study approach. The focus of this research is to identify the extent to which fiqh rules are applied in the practice of economic transactions and to understand the challenges and opportunities faced by Islamic financial institutions in their implementation. The research method used is a literature review study that involves a critical analysis of various literature sources, either in the form of scientific journals, books, or previous research reports relevant to this topic. The analysis is carried out to collect, synthesize, and evaluate the findings in the literature related to the implementation of fiqh rules in economic transactions. The results of the study show that the implementation of fiqh rules in Islamic financial institutions plays an important role in maintaining the conformity of economic transactions with Sharia principles. However, there are some challenges in its application, such as different interpretations of certain rules and a lack of in-depth understanding among practitioners. This study also found that Islamic financial institutions have a great opportunity to further optimize the application of fiqh rules through increased education and training as well as the development of innovative products. The originality of this research lies in its approach that combines various literary perspectives to provide a comprehensive overview of the application of fiqh rules in economic transactions in Islamic financial institutions. Thus, this research is expected to make a significant contribution to the development of better Islamic financial practices following Islamic principles.